TATA KELOLA MODEL IT GOVERNANCE PADA LAYANAN AKADEMIK MENGGUNAKAN FRAMEWORK COBIT 4.1 PADA DOMAIN (DELIVERY AND SUPPORT) DAN (MONITORING AND EVALUATION) - Hermawaty Hermawaty (UNIVERSITAS RAHARJA, 2017)
The role of academic information system in the High School of Information and Computer Management